Speech-Language Pathology and Audiology Professions in Asia: Past History and Current Status. - Lee, Sue Ann S.; Hui Min Ang, Chloe; Chafcouloff, Elizabeth; Seong Hee Choi; Wei De Chua, Kenneth; Krishan Cuadro, Carla; Fatimah Hani Hassan; Makoto Kariyasu; Krisna Lertsukprasert; Sasheendran, Snithin; Upik Supiaty; Meng-Ju Tsai; et al. (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: In collaboration with members of the Asia Pacific Society of Speech, Language and Hearing (APSSLH), the purpose of this tutorial was to outline a brief history and the current status of the speech-language pathology and audiology professions in Asian countries that are affiliated with the APSSLH. Method: Relevant literature and websites on the speech-language pathology and audiology professions in each country are reviewed and summarized. Information was also obtained via personal interviews. Results: A brief history, educational programs, licensure systems, and professional organizations of each country are addressed. Discussion: The developmental status of speech-language pathology and audiology professions in Asian countries varies from emerging to fully established. Several issues among countries in development are discussed, and recommendations for future development are addressed. Conclusion: This tutorial will improve awareness of speech-language pathology and audiology status in Asian countries and may facilitate ASHA and APSSLH members participation in and contributions to international relations and affairs.